A PROJECT OF CONSTRUCTING A CONTEMPORARY JEWISH IDENTITY IN RABINOVICI’S NOVEL SUCHE NACH M - Liyanti, Lisda (International Review of Humanities Studies, 2019)
Attitude to the Nazi past turns to its new phase in the 1980s, after the time of repressing, silent and mourning brings the new discourse in talking about the Holocaust. It was a tendency of "denying" the Holocaust and new anti semitism movement. In the 90s, Jewish authors confirm their position as „self determined agents' in the literary and political area. One of them is Doron Rabinovici, an Austrian Jewish author who wrote the novel Suche Nach M in engaging on the project of constructing a contemporary Jewish identity. In this article, the question of how Robinovici proposes the construction of contemporary Jewish identity will be answered through critical reading on Jewish myth and identity formation theory. The result shows two major strategies that he proposes in his novel: “deconstructs” the Jewish myth (by playing other possibilities to interpret them and unveil the truth) and suggests the self referential concept (find oneself based on 'the self' instead of immersing self in 'the Other‟). These two strategies can be seen as an active engagement with one own traumatic past. It is a historical and self awareness approach to construct a problematic contemporary Jewish identity.